Potensi Kebangkrutan Perusahaan dengan Notasi Khusus menggunakan Zmijewksi X Score Model dan Ohlson O Score Model - Hudaya, Robith; Kartikasari, Nungki; Suryantara, Adhitya Bayu; Sukma, Paradisa (Universitas Bumigora, 2024)
The Indonesian Stock Exchange (BEI) regulations in the form of Circular Letter Number: SE-00001/BEI/12-2018 require that companies be broken down into various letter notations so that their condition can be mapped. This particular notation is a warning given by the IDX to investors to protect themselves from problematic issuers and to each issuer to comply with the rules to avoid embedding more special notations. This research was conducted to map the company's potential for bankruptcy, as seen from whetherthere were financial difficulties in the year before the special notation was given. This depiction will provide initial detection for Indonesian capital market investors in investing their capital. It can serve as empirical evidence as to whether all companies previously given special notations experienced potential bankruptcy. Two financial difficulty analysis tools are used, namely the Zmijewksi X Score Model, which is based on Multiple Discriminant Analysis (MDA), and the Ohlson O Score Model, which isbased on Logistic Regression. The research results found that calculating financial distress using the X-Score model in 154 companies that received special notation found that 60 companies had the potential to experience bankruptcy. For 94 companies, there is no potential for bankruptcy in 2021. Calculation of financial distress using the O-Score model for 154 companies that received special notation found that 34 companies had the potential to experience bankruptcy. For 120 companies, there is no potential for bankruptcy in 2021. Companies with the notations E, B, Y, D and S have an enormous potential for bankruptcy. Based on these findings, investors are asked to avoid shares with this notation so as not to experience losses in investing.